Managing Romantic and Sexual Feelings Towards Clients in the Psychotherapy Room in Flanders (Belgium). (April 2023) - Vesentini, Lara; Van Puyenbroeck, Hubert; De Wachter, Dirk; Matthys, Frieda; Bilsen, Johan
It is important that therapists manage adequately their romantic and sexual feelings toward clients as it can negatively affect the psychotherapeutic relationship and may even pose a risk of sexual abuse. This study explores how psychotherapists in Flanders (Belgium) manage such feelings, by conducting both a survey (using 105 of 786 respondents for analyses, as they reported romantic feelings) and focus groups (with a total of 36 participants). Results show that most therapists never consider starting a romantic relationship with a client. They reflect profoundly on their feelings, dwell on possible consequences, while maintaining strict boundaries. Although therapists themselves highly recommend referring the client to a colleague if feelings become too intense, this rarely happens in practice. Most therapists consider talking about their romantic and sexual feelings towards clients as something very important, but only a third have disclosed their feelings in supervision, peer-supervision, or in personal therapy. Therapists indicate there is still hesitance about this due to fear of condemnation.